2015
DOI: 10.1007/s00170-015-7112-4
|View full text |Cite
|
Sign up to set email alerts
|

Forming appearance analysis in multi-layer single-pass GMAW-based additive manufacturing

Abstract: Additive manufacturing based on gas metal arc welding (GMAW) is gaining increasing popularity as the process allows fabrication of fully dense parts with high material efficiencies and deposition rates. This paper aims at studying forming characteristics of multi-layer single-pass parts. Influences of arc current, deposit velocity, and heat input on layer formation were analyzed by using a passive vision sensor. Based on the results, the arc current has the greatest effect on the forming appearance, and a bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…The mentioned authors credited this to a strong momentum of the backward flow of molten metal in the weld pool that typically occurred during high speed welding as the major factor responsible for the phenomenon, as illustrated in Figure 2. Xiong et al [10] affirmed that the quality of wall formation decreases with the arc mean current (Im) increase. On one hand, as suggested above, WFS, Im, and TS, amongst others, affect the wall quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mentioned authors credited this to a strong momentum of the backward flow of molten metal in the weld pool that typically occurred during high speed welding as the major factor responsible for the phenomenon, as illustrated in Figure 2. Xiong et al [10] affirmed that the quality of wall formation decreases with the arc mean current (Im) increase. On one hand, as suggested above, WFS, Im, and TS, amongst others, affect the wall quality.…”
Section: Introductionmentioning
confidence: 99%
“…[14]). Xiong et al [10] affirmed that the quality of wall formation decreases with the arc mean current (Im) increase. On one hand, as suggested above, WFS, Im, and TS, amongst others, affect the wall quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, the MLSP is different and complicated owing to the use of repeated heating for layer deposition. The previous layer preheats the next layer, while each new layer post-heats the previous layer [17]. The subsequent layers were deposited using the same profile of current, voltage, and travel speed, as explained earlier with the arc-striking currents of 190 A and 170 A, but this resulted in pool flow particularly at the arcextinguishing region, as shown in Figure 8.…”
Section: Multilayer Single-passmentioning
confidence: 99%
“…It has been observed that the current plays a vital role in the stability of pool flow, especially from the second to the fourth layers. Higher currents induce pool overflow, hence collapsing the forming appearance [17]. The parameters are stable in a single layer, become unstable for multiple layers in single passes.…”
Section: Introductionmentioning
confidence: 99%
“…However, this equipment and raw materials are usually very expensive, and not conducive to the promotion of application [2][3]. Fabrication of metal fused-coating additives manufacturing (MFCAM) is a new method for fabricating three-dimensional metal functional components [4].…”
Section: Introductionmentioning
confidence: 99%